Thermodynamic Characteristics of Methane Adsorption of Coal with Different Initial Gas Pressures at Different Temperatures. (7th March 2019) - Cai, Tingting; Feng, Zengchao; Jiang, Yulong; Zhao, Dong
Abstract : The adsorption of methane in coal depends on both pressure and temperature, and the adsorption gas content decreases as the temperature rises while increases as the pressure increases. When the gas molecule switches between the free state and adsorbed state, energy exchange is accompanied. To study the thermodynamic characteristics (adsorption heat, adsorption content, and adsorption time) of the methane adsorption of coal, the isothermal methane adsorption experiments of coal with different initial free gas pressures at different temperatures (30–90°C) were conducted. In this paper, a well-defined mathematical function of the adsorption heat was established on the basis of the actual gas state equation, Boltzmann energy distribution theory, and the two-state energy model, and the function was verified by the experimental data. The results show that the mathematical function of the adsorption heat can well describe the relationship among the adsorption heat, temperature, and initial free gas pressure in the closed adsorption system, and the adsorption heat involves the initial free gas pressure. The greater the initial free gas pressure, the less the adsorption heat is. In the adsorption process with different initial free gas pressures at different temperatures, the real-time free gas content increases with time and the adsorption system shows desorption process generally. For the adsorption process with the same initial free gas pressure, the adsorption time increases with the rising temperature. For the adsorption process with different initial free gas pressures at the same temperature, the greater the initial free gas pressure, the shorter the adsorption time it takes to reach an equilibrium state. The results help to understand the thermodynamic characteristics and the heat and mass transfer of methane in coal adsorption.